The Development of Academic Achievement in Social Studies Subjects in Various Regions in Asia of Mathayom Suksa 1 StudentsUsing a 5 - Step Quest for Knowledge (5E) - เพ็ชรอินทร์, ปภาวรา (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2021)
The objectives of this research are 1) to compare the learning achievement in social studies of Mathayomsuksa 1 students before and after study who received a 5-step quest for knowledge (5E) 2) to study the progress of the social studies academic results of Mathayomsuksa 1 students who received a 5-step quest for knowledge (5E). The sample consisted of 37 students in Mathayom Suksa 1/7, which were obtained by simple random sampling. The tools used in this research consisted of 1) social studies learning management plan, the quality level is at a very appropriate level 2) the achievement test, regions in asia social studies courses Mathayomsuksa 1, grade 20 items. The statistics used for data analysis were percentage and t - test.The results were as follows: 1) Mathayom Suksa 1 students who received a 5-step (5E) quest for knowledge had a statistically higher achievement of post-study social studies at the .05 level.2) Mathayomsuksa 1 students who received a 5-step (5E) quest for knowledge management had a percentage of progress of social studies academic achievement higher than the threshold, representing 36.80%. and 3) Mathayomsuksa 1 students who received a 5-step (5E) quest for knowledge management had an increased individual progress score in the Social Studies subject. Has a mean of 7.36.